Development of an effective control and management system at a shipbuilding enterprise - A. Yu. Yanchenko; E. A. Lyashenko (Путеводитель предпринимателя)
The article updates the importance of the control system for management purposes. The essence of control, its types, characteristics, as well as difficulties in organizing an objective control system are specified. The process of digital transformation of the system of control and management of production assets of a shipbuilding enterprise is considered. The advantages of information technologies based on management standards and geographic information system are detailed.